Depression and anxiety as predictors of performance status and life satisfaction in older adult neurological patients: a cross-sectional cohort study - Głowacka, Mariola; Przybyła, Natalia; Humańska, Marzena; Kornatowski, Maciej (Frontiers in Psychiatry, 2024)
Neurological disorders are one of the leading causes of disability globally. Studies emphasise that the course and effectiveness of rehabilitation interventions may be influenced by emotional factors. The aim of the present study was to assess the prevalence of depressive and anxiety symptoms in patients with neurological disorders and examine whether depression and tendency to respond with anxiety are predictors of disability in these patients. The study included 229 individuals with neurological disorders aged over 55. Our findings show that stroke patients are more likely to experience depressive symptoms and are more likely to display trait anxiety as compared with patients with other neurological disorders. Advanced age, female sex, low level of education and the presence of trait anxiety are associated with a higher severity of depressive symptoms. Stroke survivors have significantly poorer ECOG performance scores and are more likely to be incapable for work. Both depression and trait anxiety are significant predictors of neurological patients’ performance status, and the presence of depressive symptoms is a determinant of these patients’ level of satisfaction with life. An understanding of psychological risk factors for poorer performance status in individuals with neurological disorders will make it possible to plan prophylactic interventions in order to minimise negative health impacts and facilitate access to mental health facilities.